Survey of cooking practices and methods for beef steaks and roasts - L.J. Franken; E.J. Harvey; C. Pearsall; James L. Marsden; Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 2005)
To support the development of Good Manufacturing Practices for the use of mechanical tenderization in the meat processing industry, a questionnaire was distributed to home, retail, and institutional preparers of beef steaks and roasts. Five hundred individuals in the United States were surveyed on their cooking practices and methods for preparing steaks and roasts. The survey was circulated to individuals from seven states, and consisted of nine questions that addressed where and how participants cooked steaks and roasts. Survey participants were directed to answer all questions that pertained to them and their methods for cooking of steaks and roasts. Results indicated that most participants used color as an indicator of doneness of steaks, whereas cooking time was most often used to indicate doneness of roasts. None of those who were surveyed knew the recommended minimum internal temperature (145°F) for cooking steaks or roasts.
Keywords: Cattlemen' s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Cooking practices; Steak; Roasts